Helipot Alumina microcircuit chips with ruler - Dietrich, T. A. (1950)
This photograph is part of a series of marketing images used to demonstrate the small size of Helipot products.
Keywords: Microelectronics; Rulers (Instruments); Beckman Instruments, Inc.